The Antidiabetic Potential of Ruellia tuberosa L. - Putri Fatmawati; Siti Nur Afiyah (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2024)
Diabetes mellitus (DM) is a metabolic condition characterized by insufficient insulin production or resistance to insulin, resulting in elevated blood sugar levels. Several synthetic medications, such as Acarbose, Metformin, Glibenclamide, Miglitol, and Voglibose, are presently employed to manage high blood sugar levels. However, these drugs have many side effects, causing some mild to severe adverse effects, including gastrointestinal symptoms, nausea, and vomiting. Hence, it is crucial to research natural products as promising antidiabetic alternatives. This study aimed to provide a comprehensive overview of the potential of Ruellia tuberosa L. as an antidiabetic drug candidate based on the secondary metabolite compounds contained in it. The literature review process involved searching specific keywords in various databases, including Google Scholar, the GARUDA portal, ScienceDirect, PubMed, and DOAJ. All incomplete, duplicates, and pay-access articles were filtered out, and inclusion criteria were applied. The result of this study shows that Ruellia tuberosa L. secondary metabolite compounds are alkaloids, amino acids, ascorbic acids, carbohydrates, flavonoids, glycosides, phenolics, quinoline, saponins, steroids, sterols, tannins, and terpenoids. In silico molecular docking analysis and in vivo testing of Ruellia tuberosa L. extract on streptozotocin (STZ)-induced diabetic Wistar rats show that Ruellia tuberosa L. has the potential to be developed as an antidiabetic alternative drug.